THE DRIVING FACTORS OF CUSTOMER LOYALTY: STUDY ON B2B CUSTOMERS - Eva Kuniasih; Ari Setiyaningrum (STIE Pelita Nusantara Semarang, 2023)
This study aims to examine the factors that determine customer loyalty to business customers. In particular, this study examines the effect of service quality and product quality on customer loyalty directly and indirectly through customer satisfaction mediation. Primary data collection was carried out by surveying through the distribution of questionnaires to 50 companies at oil and gas industry in Indonesia. Sampling was done by purposive sampling technique. The results of hypothesis testing with SEM-PLS indicated that service quality and product quality have a direct effect on customer loyalty. The results of the indirect effect test prove that customer satisfaction partially mediates the effect of service quality and product quality on customer loyalty.